Resiliency in adolescents at high-risk for substance abuse: flexible adaptation via subthalamic nucleus and linkage to drinking and drug use in early adulthood - Weiland, Barbara J. (2012)
INTRODUCTION: The personality trait resiliency is the ability to flexibly adapt impulse control relative to contextual demand. Low resiliency has been linked to later alcohol/drug problems. The underlying psychological and neural mechanisms are unknown but neurocomputational models suggested relations between resiliency and working memory. Cortical-striatal connectivity has been proposed to underlie adaptive switches between cautious and risky behaviors. METHODS: Working memory was probed in sixty-seven 18–22 year olds from a larger community study of alcoholism, using the n-back task during functional magnetic resonance imaging. Functional connectivity between task-related regions was investigated with psychophysiological interaction analysis. Resiliency was measured in early teen years and related to early adulthood measures of drinking/drug use, task activation and connectivity. Relationships with risk factors, including family history, age of drinking onset and number of alcohol problems were also investigated. RESULTS: Higher resiliency was related to lower levels of substance use, fewer alcohol problems and better working memory performance. Whole brain regression revealed resiliency negatively correlated with activation of subthalamic nucleus (STN) and pallidum during the n-back. High and Low resiliency quartile groups (n=17 each) differed in coupling strength between STN and median cingulate cortex, a region of reduced activation during working memory. The High resiliency group had later onset of drinking, fewer alcohol problems, had used fewer illicit drugs and were less likely to smoke cigarettes than their Low resiliency counterparts, CONCLUSIONS: These findings suggest that resiliency in early adolescence may protect against alcohol problems and drug use, though the direction of this effect is currently unknown. This protective factor may relate to executive functioning as supported by the finding of a neural link shared between resiliency and working memory in basal ganglia structures. The STN, a key basal ganglia structure, may adaptively link flexible impulse control with cognitive processing, potentially modulating substance use outcomes.